Looking for Starmerism. Issue 2 (6th May 2021) - Fielding, Steven
Abstract: Most of those trying to assess what Keir Starmer stands for and how he plans to achieve his objectives are too impressed by an understanding of Thatcherism associated with Stuart Hall. That is one reason why they complain that Starmerism is little more than an empty space. But other less heroic ways of thinking about a leader's 'ism' are available and using a more multidimensional approach, this article assesses the evolution of Starmerism through his successful campaign to be leader of a divided party and his first year as leader of the opposition. On that basis it suggests that Starmerism as currently articulated is close to a 'Corbynism with the brakes on', although if it is to resonate with the public, Starmer himself needs to adopt some of the rhetorical tools associated with Wilsonism at its peak.